Effect on the innate aerobic capacity or acrobatic training on the inflammation of the brain in rats - Honkanen, Markus (2019)
A mammal body reacts to the invader via an inflammation reaction. Immune system in brain is special because of the blood-brain barrier and glial cells. Hippocampal neurogenesis produces new neural cells. The rate of neurogenesis can be elevated by aerobic exercise and skill learning. Inflammation is detrimental to the neurogenesis and learning. Western blot is often used as a tool for study of inflammation and neurogenesis, but lack of validation studies and uniform protocols causes uncertainty to results. High aerobic capacity should protect from inflammation and enhance learning. The purpose of the thesis was to study a connection with an intrinsic aerobic capacity, age or acrobatic training and inflammation or synaptic plasticity in the rat brain. Also inter-user variability and difference between two western blot devices and softwares were studied. 19 high aerobic capacity (HCR) and 20 low aerobic capacity (LCR) sedentary male rats were killed at the age of 8 or 40 weeks. 24 Sprague-Dawley rats were divided to the acrobatic training (Acro) and control (Ctrl) groups for 8 weeks of acrobatic training intervention. Quantitative western blotting analysis was made for protein homogenates of left hippocampi. Antibodies for brain inflammation and synaptic plasticity were used. Two analysts quantified results of three antibodies and between two devices and softwares for methodological comparison. The LCR rats expressed more inflammation markers than the HCR rats in overall. The age comparison resulted inconsistent outcome. Synaptic plasticity results were contradictory. There were no differences between the Acro and Ctrl groups in inflammation markers or in synaptic plasticity. In the method comparison, SYN-1 results were consistent regardless the analyst or device. IBA1 resulted moderate correlations in comparisons. SYP resulted high inter- user correlation but lower inter-device correlation. Higher aerobic capacity of the HCR rats reduces brain inflammation compared to the LCR rats. Differences in aerobic capacity and inflammation markers are present already at young age, but results were inconsistent. Contradictories in synaptic plasticity results leads to no conclusion with effect of aerobic capacity to learning. Acrobatic training did not result marked differences in this study. Reliability of western blotting results between analysts and devices depend on the antibody used. To ensure reliable results, one analyst should execute all the tests in a study using the same device and software. Results should also be confirmed using some other method.